Behaviour and strength assessment of masonry prisms. (June 2018) - Thaickavil, Nassif Nazeer; Thomas, Job
Graphical abstract: Highlights: Tested 192 masonry prism specimens corresponding to three specimens each in 64 groups. Test variables are Masonry units (two types), Mortar strength (four types), Joint configurations (eight types). Reported strength and cracking pattern of prisms. Model accounting for Unit strength, Mortar strength, Volume fraction of unit, Volume ratio of bed joint to mortar and Height-to-Thickness ratio. Carried out regression analysis of 232 data which include 64 test data of present study and 168 data reported in the literature. Abstract: This is a case study presenting the cracking behavior and assessment of the compressive strength of masonry prisms. The compressive strength of masonry was determined by performing laboratory tests on 192 masonry prism specimens corresponding to 3 specimens each in 64 groups. The variables considered in the experimental program are type of brick, strength of masonry and height-to-thickness ( h/t ) ratio of the prism specimen. Pressed earth bricks and burnt clay bricks were used for the preparation of masonry prisms. A mathematical model is also proposed for the estimation of compressive strength of masonry prisms by performing a statistical multiple regression analysis on 232 data sets, which includes 64 test data from the present study and 168 test data published in the literature. The model was developed based on the regression analysis of test data of prisms made of a variety of masonry units namely clay bricks, pressed earth bricks, concrete blocks, calcium silicate bricks, stone blocks, perforated bricks and soft mud bricks. The proposed model not only accounts for the wide ranges of compressive strengths of masonry unit and mortar, but also accounts for the influence of volume fractions of masonry unit and mortar in addition to the height-to-thickness ratio. The predicted compressive strength of prisms using the proposed model is compared with 14 models available in published literature. The predicted strength was found to be in good agreement with the corresponding experimental data.